Dissemination of trial results to participants in phase III pragmatic clinical trials: an audit of trial investigators intentions - Katie Gillies; M Zulfiqar Raza; Hanne Bruhn (BMJ Open)
Objective To determine the proportion of Phase III clinical trials given a favourable opinion by a research ethics committee in the UK that provided trial results to those who participated.Design Audit of records.Setting Phase III clinical trials registered on the UK’s research permissions system (Integrated Research Application System) between the 1 January 2012 to 31 December 2017.Main outcome measures Proportion of trial investigators that intended to provide results to trial participants compared against what trials reported to ethics committees at the end of study.Results Out of 1404 Phase III trials, 87.7% (n=1231) trials stated they intended to disseminate results to participants while 12.3% (n=173) trials stated they would not. Out of these 1231 trials, 18.8% (n=231) trials intended to actively communicate trial results or a means of accessing results to their participants, a further 80.5% (n=991) reported passive intention to disseminate and for the remainder (n=9) the process was unclear. Of the 370 End of Study reports (30% of all included studies) that could be accessed 10 (2.7%) explicitly mentioned activities related to dissemination of findings to participants with the majority (74.9%) having no mention and a further 22.4% of reports not being accessible. Of the 10 which did report dissemination of results to participants the majority (n=6) were through a lay summary or letter.Conclusions Reported intention to disseminate results to trial participants among trial investigators is high, however, reporting of feedback methods is lacking. In addition, mechanisms to ensure intentions to disseminate trial results are translated into actual behaviour need to be put in place to ensure those who participate in trials have the opportunity to find out about the results.